2006
DOI: 10.1111/j.1600-0854.2006.00389.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Function of Phospholipase D and Phosphatidic Acid During Phagocytosis

Abstract: Phospholipase D (PLD) produces phosphatidic acid (PA), an established intracellular signalling lipid that has been also implicated in vesicular trafficking, and as such, PLD could play multiple roles during phagocytosis. Using an RNA interference strategy, we show that endogenous PLD1 and PLD2 are necessary for efficient phagocytosis in murine macrophages, in line with results obtained with wild-type constructs and catalytically inactive PLD mutants which, respectively, enhance and inhibit phagocytosis. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
129
2
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 131 publications
(140 citation statements)
references
References 47 publications
6
129
2
3
Order By: Relevance
“…Rat RSK2 cDNA fragments encoding the 21-nt siRNA sequence CTGAAGAAGGCAGTATCAAAG (identical in rat and bovine) derived from the target transcript or the mutated cDNA fragment CTCTAGAAGGCAG-TATCAAAG, separated from their reverse 19-nt complement by a short spacer, were annealed and cloned in the BglII and HindIII sites in front of the H1 promoter of either the pEGFP-N2-RNAi plasmid or a modified pXGH5 plasmid encoding GH (pGHsuper) as described (13). PLD1 siRNA and PLD1 rescue plamids have been described (12). T147 mutants were obtained by sitedirected mutagenesis as described (37).…”
Section: Methodsmentioning
confidence: 99%
“…Rat RSK2 cDNA fragments encoding the 21-nt siRNA sequence CTGAAGAAGGCAGTATCAAAG (identical in rat and bovine) derived from the target transcript or the mutated cDNA fragment CTCTAGAAGGCAG-TATCAAAG, separated from their reverse 19-nt complement by a short spacer, were annealed and cloned in the BglII and HindIII sites in front of the H1 promoter of either the pEGFP-N2-RNAi plasmid or a modified pXGH5 plasmid encoding GH (pGHsuper) as described (13). PLD1 siRNA and PLD1 rescue plamids have been described (12). T147 mutants were obtained by sitedirected mutagenesis as described (37).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown before that PA induces a large fusogenic effect in membranes of several cell systems (48,49). Vesicular trafficking and exocytosis are all increased after membrane fusion of PA in vivo (7). PA location within the cell should be crucial to the production of movement.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphatidic acid (PA) is a pleiotropic lipid second messenger in yeast, plants, and mammalian cells. In the latter it has been shown that vesicular trafficking and exocytosis are increased through promotion of membrane fusion by PA in vivo (7). PA also causes the formation of transformed colonies in soft agar or tumors in xenografted nude mice of H-RasV12 oncogene-transfected fibroblasts (8).…”
mentioning
confidence: 98%
“…The assembly of the phagocytic cup appears to be controlled indirectly by regulators of small GTPases, such as the Rac GAP ARHGAP25 (Csépányi-Kömi et al, 2012) and the Rho GEF VAV2 (Arora et al, 2008). Interestingly, during their establishment, both the macropinocytic and phagocytic cups require an expansion of their limiting membrane, and this happens by the exocytosis of specific cytoplasmic vesicles (Falcone et al, 2006;Corrotte et al, 2006).…”
Section: Sculpting Of Membrane Invaginationsmentioning
confidence: 99%